Mao Zedong, China and Black Liberation. Issue 3 (3rd July 2021) - Pateman, Joe
ABSTRACT: Since Black Lives Matter (BLM) rose to prominence, liberal democracies have been internally divided over their response to the movement. Whilst some politicians have supported BLM's struggle against anti-black racism, others have condemned it as unnecessary, or even harmful to democracy. China, by contrast, has displayed unwavering solidarity with BLM, by providing it with official coverage and support. In an attempt to discredit these efforts, liberals have portrayed China's solidarity statements as pragmatic gestures, designed to draw attention away from its alleged human rights violations. This article shows that these accusations are baseless. China's support for the black liberation struggle precedes BLM; and is rooted in the revolutionary internationalism of its founder, Mao Zedong. Under the leadership of the Communist Party of China, the Chinese state has developed Mao's Marxist analysis of the African American struggle. In doing so, China has helped BLM expose the racist core of US capitalism.